Hidromedusas mesozooplanctónicas del océano Pacífico colombiano - Ángela María-Baldrich; Raúl H. López (Biota Colombiana, 2010)
Within the marine zooplankton hydromedusae have a high taxonomic and an ecological significance, despite which little is known about these organisms for the Colombian Pacific Ocean (OPC). For these reasons, among others, the first list of genera and species for this region is presented. An intensive literature review of previous work in the OPC was accomplished; also 158 samples of mesozooplankton obtained during six oceanographic cruises of the Regional Study of the phenomenon known as âEl NiÃ±oâ (ERFEN) undertaken from 2001 to 2005 were examined. 6072 hydromedusae were captured, of which 6003 were identified. From this information, plus that obtained in the literature, it was concluded that to date 27 genera and 40 species for the OPC have been identified.